Digital hostility, subjectivity and ethics: Theorising the disruption of identity in instances of mass online abuse and hate speech. (April 2023) - Cover, Rob
The experience of hostility, hate speech and adversarial behaviour in everyday online spaces has increased substantially in recent years, with known health and mental health outcomes for users. This paper argues that due to the 'massified' form of contemporary hostility experienced in the internet 'pile on', a new framework for understanding and remedying hostility is required. This paper draws on Judith Butler's theories of identity to present an account of digital hostility as cultural and as having a negative effect on the identities and selfhood of users. It discusses the impact of the online pile-on, shaming and the ways in which hostility positions victims as ungrievable subjects. The essay recommends new ethical approaches grounded in the recognition of subjects as vulnerable, arguing that cultural ethics approaches are valuable not only as public pedagogies but for development of technological solutions and moderation interventions to help prevent hostility and hate speech.